Influence of in-situ NH3 plasma passivation on the electrical characteristics of Ga-face n-GaN MOS capacitor with atomic layer deposited HfO2. (November 2018) - Jung, Woo Suk; Lim, Donghwan; Han, Hoonhee; Sokolov, Andrey Sergeevich; Jeon, Yu-Rim; Choi, Changhwan
Highlights: In-situ NH3 plasma passivation for Ga-face n-GaN MOS capacitor was done by varying plasma power and exposure time. Improvement in frequency dispersion, ΔVFB, Jg, Cox, and Dit . Residual carbon and sub GaOx are efficiently suppressed and defects are passivated. Abstract: The effects of in-situ NH3 plasma passivation on the interface between atomic layer deposited HfO2 and Ga-face n-GaN substrate in metal-oxidesemiconductor (MOS) devices were investigated by varying plasma power and exposure time and compared with GaN MOS device without plasma passivation. ALD HfO2 -GaN device with in-situ NH3 plasma treatment shows improved electrical characteristics including negligible frequency dispersion at the near flat-band voltage region, lower hysteresis (∼10 mV), suppressed oxide capacitance dispersion in the accumulation (2.2%), lower leakage current density (5.21 × 10 −2  A/cm 2 at 1 V), and low interface state density (Dit ) of ∼6.77 × 10 11  eV −1  cm −2 at Ec -Et  = 0.3 eV using an optimized plasma passivation exposure time of 10 min and power of 50 W. These results are attributed that NH3 plasma treatment could eliminate carbon species and detrimental sub-GaOx as well as passivate the surface and bulk defects on GaN caused by Ga-N dissociation.